2017
DOI: 10.1093/jjco/hyx073
|View full text |Cite
|
Sign up to set email alerts
|

miR-582-5p inhibits invasion and migration of salivary adenoid cystic carcinoma cells by targeting FOXC1

Abstract: miR-582-5p could suppress effect on the process of invasion and migration in SACC cell lines, and this could occur through its target gene FOXC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Similarly, miR-582-5p acts as the tumor suppressor by targeting Rab27a in human colorectal carcinoma 22. Recently, miR-582-5p was reported to inhibit invasion and migration of salivary adenoid cystic carcinoma cells by targeting FOXC1 23. In cervical squamous cell carcinoma, mir-582 was reported to be reduced 24.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-582-5p acts as the tumor suppressor by targeting Rab27a in human colorectal carcinoma 22. Recently, miR-582-5p was reported to inhibit invasion and migration of salivary adenoid cystic carcinoma cells by targeting FOXC1 23. In cervical squamous cell carcinoma, mir-582 was reported to be reduced 24.…”
Section: Discussionmentioning
confidence: 99%
“…Further mechanism study showed that miR-582-5p exerted the inhibitory effect through targeting AKT3[22]. Study by Wang et al described that miR-582-5p suppressed metastasis of salivary adenoid cystic carcinoma cells via targeting FOXC1[9]. In gastric cancer, miR-582-5p has been verified to restrain cell growth by down-regulating the expression of AKT3[23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that miR-582-5p exerts dual function against different kinds of tumors. For example, Wang et al[9] proved that miR-582-5p inhibits invasion and migration of salivary adenoid cystic carcinoma cells. Study by Zhang et al[10] showed that upregulation of miR-582-5p inhibits cell proliferation, cell cycle progression and invasion in human colorectal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In thyroid carcinoma, researchers found that the expression of miR-577 was significantly down-regulated in TC tissue and TC-1 cell lines, then up-regulating the expression of miR-577 and targeting the supression of SphK2 could inhibit the proliferation, invasion, and migration abilities of TC-1 cell lines in vitro [9]. In addition, miR-582-5p significantly down-regulated in the salivary adenoid cystic carcinoma and significantly influenced the proliferation, invasion, and migration abilities of salivary adenoid cystic carcinoma cells by targeting FOXC1 [10]. RAB23, a class of Ras-related small GTPase family, was first extracted from the brain, and subsequently the role of RAB23 was reported in multiple types of tumour and was demonstrated to be involved in the development and occurrence of lung cancer, liver cancer, gastric cancer, and breast cancer, as well as being closely related to cancer progression [11,12].…”
Section: Introductionmentioning
confidence: 99%